Managing corporate social responsibility : a communication approach - Coombs, W Timothy (Wiley-Blackwell, 2015)
"Managing Corporate Social Responsibility offers a strategic, communication-centred approach to integrating CSR into organizations. Drawing from a variety of disciplines and written in a highly accessible style, the book guides readers in a focused progression providing the key points they need to successfully navigate the benefits and implications of managing CSR. Chapters are organized around a process model for